Official Languages Recognition Program (OLRP) - Accreditation Canada (2022)
Accreditation Canada’s Official Languages Recognition Program (OLRP) supports and awards organizations that are committed to improving access to health and social services in official languages. This brochure answers questions such as: - How does the program work? - How does this program integrate with our current language accessibility efforts? - Who developed this program? - Why is this the right time to participate? - How much does it cost to participate in the program?

Programme de reconnaissance des langues officielles (PRLO) - Agrément Canada (2022)
Le Programme de reconnaissance des langues officielles (PRLO) d'Agrément Canada appuie et certifie les organismes qui sont engagés à améliorer l'accès aux services de santé et services sociaux en langues officielles. Ce feuillet d'information à l'intention des fournisseurs de services répond aux questions suivantes: - Comment le programme fonctionne‐t‐il ? - Comment ce programme s'intègre-t-il à nos efforts actuels d'accessibilité linguistique ? - Qui a élaboré ce programme ? - Pourquoi est-ce le bon moment de participer ? - Quel est le coût pour participer au programme ?

A comparison of two phonological screening tools for French-speaking children - Bérubé, Daniel; Macleod, Andrea A. N. (International Journal of Speech-Language Pathology, 2022)
Purpose: To examine two screening tools for phonological production, the Evaluation Sommaire de la Phonologie chez l’enfant d’âge préscolaire (ESPP) and the Test de Phonologie du Français Canadien-Dépistage (TPFC-D), developed according to differing theoretical perspectives. The TPFC-D, designed according to nonlinear phonology, includes more words and contains a greater variety of segments across word structure as compared to the ESPP, which was guided by a linear phonological framework. The greater response rate to test items, time of administration, and phonological complexity were expected on the TPFC-D. Method: Each screening tool was administered to 14 4-year-old French-speaking children living in Central Canada. Paired samples t-tests compared children’s responses on the two tasks with regards to (a) response rate and time of administration, (b) an overall percentage of consonants correct (PCC) and percentage of vowel correct (PVC), and (c) complexity of productions (i.e. PCC and PVC in relation to word structure, Word Shape Match, Whole Word Match, Phonological Mean Length of Utterance (pMLU) and Proportion of Whole-Word Proximity). Result: Item response rates were higher for the TPFC-D whereas time of administration, PCC and PVC were similar for both the ESPP and TPFC-D. Complexity measures showed a higher proportion of deletions in clusters and higher pMLUs on the TPFC-D compared to the ESPP. Conclusion: Both screening measures are appropriate for speech-language pathologists who want to assess quickly pre-school-aged children. Since the TPFC-D is phonologically more complex, it is recommended for clinicians needing to screen children who likely present with multiple speech sound errors across their phonological system.

La discordance linguistique. L'intervenant et le patient ne parlent pas la même langue ou ne peuvent pas communiquer adéquatement [infographie] - Consortium national de formation en santé (2022)

Guide de la personne aidante - Fédération des femmes acadiennes de la Nouvelle-Écosse (2022)

Access to Health and Social Services in Official Languages (Reaffirmation) - Health Standards Organization (2022)
The standard CAN/HSO 11012:2018 (R2022) is a reaffirmation of CAN/HSO 11012:2018 Access to Health and Social Services in Official Languages. The standard provides guidelines of excellence to help organizations aim to improve access to health and social services across the continuum of care in Canada’s two official languages – French and English. The standard content is grouped into five sections: - Establishing the Active Offer of Services - Clinical Research - Governance and Leadership - Workforce - Quality Assurance

Accès aux services de santé et aux services sociaux dans les langues officielles (confirmation) - Health Standards Organization / Organisation de normes en santé (2022)
La norme CAN/HSO 11012:2018 (R2022) est une confirmation de la norme CAN/HSO 11012:2018 intitulée Accès aux services de santé et aux services sociaux dans les langues officielles. Elle fournit des lignes directrices d’excellence pour aider les organismes à améliorer l’accès aux services de santé et aux services sociaux à l’intérieur du continuum de soins dans les deux langues officielles du Canada, soit le français et l’anglais. Le contenu de la norme comprend cinq sections : - Établissement de l’offre active de services - Recherche clinique - Gouvernance et leadership - Main-d’oeuvre - Assurance de la qualité

Problèmes d’accès aux services en français ? Contactez-nous. Nous pouvons vous aider [infographie] - Ombudsman de l'Ontario (2022)

Problems accessing services in French? Contact us. We can help [infographie] - Ontario Ombudsman (2022)

Je suis insatisfait(e) des services de santé reçus. Que faire ? Comment procéder ? [infographie] - Réseau des services de santé en français de l'Est de l'Ontario; Santé Canada; Société Santé en français (2022)

Boîte à outils virtuelle de soins culturellement adaptés pour les francophones dans les foyers de SLD - Réseau du mieux-être francophone du Nord de l’Ontario (2022)

Carte interactive- Le Nouveau-Brunswick - Réseau en immigration francophone du Nouveau-Brunswick (2022)
Ce site présente une carte interactive qui permet de rechercher différents services, dont les services de santé, disponibles en français au Nouveau-Brunswick

Guide santé pour les nouveaux arrivants en Nouvelle-Écosse - Réseau santé en Nouvelle-Écosse, Immigration francophone Nouvelle-Écosse et Réseau en immigration francophone de la Nouvelle-Écosse (2022)

Guide santé pour les nouveaux arrivants aux territoires du Nord-Ouest - Réseau TNO Santé (2022)

Passeport santé pour les nouveaux arrivants aux Territoires du Nord-Ouest - Réseau TNO Santé (2022)

Évaluation de la mise en œuvre de services en français en contexte minoritaire : développement d’un questionnaire sur l’expérience des usagers - Sauvé-Schenk, Katrine; Savard, Jacinthe; Savard, Sébastien; Prud’homme, Denis; van Kemenade, Solange; Le Callonnec, Lucie; Pignac, Sarah (2022)